2014
DOI: 10.1039/c3dt52282b
|View full text |Cite
|
Sign up to set email alerts
|

Towards a quantitative understanding of palladium metal scavenger performance: an electronic structure calculation approach

Abstract: Dispersion corrected density functional theory (DFT-D) has been applied to understand the performance of several palladium metal scavengers. Nine different sulfur-based ligands and three different palladium metal sets have been investigated in detail. Based on a thorough analysis of the thermodynamic binding parameters ΔH, ΔG and ΔS, we have identified the best binding modes for all scavenger ligands. Bis-monodentate coordination is favoured over chelation in ΔH and ΔG values for most of the scavenger ligands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Scavenger screening studies within the pharmaceutical industry have regularly found SPM32 and other multifunctional silica scavengers to be more efficient for Pd removal and a computational study has recently been conducted to better understand the importance of the thioether unit in this regard. 27 The functional group loading (FGL) of the SPM32 scavenger comprises between 0.8 and 1.1 mmol of functional group per gram of silica, with the FGL of the particular batch of scavenger used in this study measured at 0.93 mmol/g (see section 2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Scavenger screening studies within the pharmaceutical industry have regularly found SPM32 and other multifunctional silica scavengers to be more efficient for Pd removal and a computational study has recently been conducted to better understand the importance of the thioether unit in this regard. 27 The functional group loading (FGL) of the SPM32 scavenger comprises between 0.8 and 1.1 mmol of functional group per gram of silica, with the FGL of the particular batch of scavenger used in this study measured at 0.93 mmol/g (see section 2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The column packing material, a silica-based thiol-functionalized scavenger, is used to break down Pd complexes in solution and promote binding to the metal. Recent publications , reported that Pd speciation affects the performance of metal scavenging processes. The detrimental impact of dissolved oxygen to scavenging performance has been confirmed experimentally in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, process chemists must develop a specific and highly efficient palladium-scavenging protocol for each API to meet the safety regulation. This is accomplished through screenings of dozens of potential workup protocols and scavengers, among other purification techniques. This process generates several dozens of samples in which to quantify palladium. Meanwhile, new scavengers continue to emerge, , adding options to explore.…”
Section: Introductionmentioning
confidence: 99%